Terrorism in Africa the evolving front in the War on Terror - Davis, John, 1962- (Lexington Books, 2010)
The study, Terrorism in Africa: The Evolving Front in the War on Terrorism, represents a research endeavor aimed at increasing scholarly discourse on the ever-expanding threat of terrorism and terrorist-related violence in the region. It offers the most wide-ranging analysis of the sub-national and transnational terrorists groups that have made Africa the second most violent region in the world. Additionally, the study expands the coverage of the multiple dynamics that indicate why terrorist-related violence continues to increase in the region and closes with regional solutions to the threat of terrorism.